2016
DOI: 10.1007/s13197-016-2264-2
|View full text |Cite
|
Sign up to set email alerts
|

Bio-fortification and shelf-life extension of idli batter using curry leaves (Murraya koenigii)

Abstract: Among several traditional foods of India, idli is one of the most popular and commonly consumed steamed products. A new method of adding Murraya koenigii (curry leaves) to idli batter as a vehicle for fortification and extension of shelf-life has been developed. Dried curry leaves powder was incorporated with other ingredients like rice and dehusked black gram in different proportions to optimize the most palatable formulation. Rate of fermentation and microbial changes in the batter; nutritional qualities, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
(16 reference statements)
2
9
0
Order By: Relevance
“…The decrease in viscosity of idli batter stored at 30 and 4°C are depicted in Fig. 1e, f. It has been reported that idli batter without the addition of preservative or stabilizers showed decrease in the viscosity at both ambient (30°C) and refrigerated storage conditions (Nisha et al 2005;Chelliah et al 2016). In the present study, idli batter incorporated with mustard essential oil had a significantly higher viscosity than the control sample stored at 30°C for 5 days and at 4°C for 30 days.…”
Section: Viscosity Of Idli Battersupporting
confidence: 59%
“…The decrease in viscosity of idli batter stored at 30 and 4°C are depicted in Fig. 1e, f. It has been reported that idli batter without the addition of preservative or stabilizers showed decrease in the viscosity at both ambient (30°C) and refrigerated storage conditions (Nisha et al 2005;Chelliah et al 2016). In the present study, idli batter incorporated with mustard essential oil had a significantly higher viscosity than the control sample stored at 30°C for 5 days and at 4°C for 30 days.…”
Section: Viscosity Of Idli Battersupporting
confidence: 59%
“…Nowadays in the market, there is a huge demand for ready-to-cook packaged idli batter which have a moderate shelf life. For extending the shelf life of packaged idli batter there are few thermal preservation techniques used which improves the shelf life of idli batter more than two to three days at room temperature and up to one month in refrigerated conditions [8][9][10][11]. Those techniques are not viable it coagulates the idli batter or due to heat applications idli will be formed.…”
Section: Introductionmentioning
confidence: 99%
“…M. koenigii berries extract was also encapsulated in the double emulsion for prolonged antioxidant effect (Kumar & Kumar, 2020). It has also been utilized in biofortification and shelf life extension (Chelliah et al, 2016) of idli batter (traditional Indian food) and nutritionally enhanced chutney powder (Balaswamy et al, 2004). Other than these, M. koenigii raw leaves and extracts were also utilized as an ingredient for promoting antioxidant and prebiotic potential .…”
Section: Introductionmentioning
confidence: 99%